Social Contribution and Psychological Well-Being among Midlife Adults with Chronic Pain: A Longitudinal Approach. (7th August 2020) - Nguyen, Nguyen P.; Kim, Shin Ye; Daheim, Jacob; Neduvelil, Ashley
Objectives: Contributing to the welfare of others has been shown to have positive effects on people's social and psychological well-being (PWB). The current study examined whether social contribution (SC) could alleviate the negative effects of chronic pain on PWB through perceived social support (PSS) among midlife and older adults.Methods: The study consisted of 520 participants with chronic pain from the two waves of the Midlife in the United States dataset (MIDUS II and III).Results: Results from the longitudinal moderated mediation analysis indicated that SC at Time 2 (T2) significantly buffered the negative effect of pain interference (PI) at Time 1 (T1) on PSS at T2, which indirectly alleviated the negative effect of PI at T1 on PWB at T2.Discussion: The study suggested the protective role of SC and prosocial behaviors in mitigating the detrimental effects of chronic pain on social support and PWB.